The Effect of Using Youtube Video Media in Mathematics Learning on the Understanding of Mathematical Concepts in Grade VII Students of JHS 2 Bangkinang - Cahaya Amergus; Molli Wahyuni; Zulfah Zulfah (Postgraduate School, Universitas Negeri Padang, 2021)
This research is motivated by the lack of understanding of mathematical concepts of seventh-grade students of Junior High School (JHS) 2 Bangkingan. The solution given to the problems that exist in JHS 2 Bangkingan is through the provision of youtube video media. The purpose of this study was to test how much influence the use of youtube video media in learning mathematics had on students' understanding of mathematical concepts. This pure experimental research was carried out using the Flipped Classroom learning model. This study involved two classes that were randomly assigned and given different treatments, namely the experimental group and the control group. Based on the results of research and discussion, it can be concluded that the use of youtube media has a significant effect on the mathematical understanding ability of seventh-grade students of JHS 2 Bangkingan. This is proven by the independent-test where the value of sig (2-tailed) is 0.004 < 0.05.